Pembinaan Kesehatan Reproduksi Remaja Berencana - Gabriela Advitri Febriani (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Population in Indonesia in 2020 is 270,203,917 people with the number of teenagers (aged 10-19 years) as many as 46 million (17%). This large number of adolescents requires special attention from all parties, considering that adolescents are an age group that is vulnerable to the Three Basic Risks of Adolescent Reproductive Health Threats. The purpose of this community service is to educate adolescents about the importance of awareness in maintaining their reproductive health. This community service activity is in collaboration with the Information and Counseling Center for Adolescent Reproductive Health Rafflesia Singkawang Timur Districts, which was held on March 27, 2022, took place at the Singkawang City Regional Mess Court with a total of 24 male and female adolescents from Singkawang City. The method of activity is in the form of counseling through demonstrations, games, questions and answers and discussions. The counseling activity begins with a question and answer (pre-test). After counseling and discussion, a post-test was carried out and the result was an increase in knowledge with an average value of 77.6. This proves the need for special attention for adolescents to understand the importance of maintaining reproductive health in order to avoid the Three Basic Risks of Adolescent Reproductive Health Threats.